An Implementation of Internet of Things for Digitalization of Kanban Production System - Purba, Victor Chris Samuel; Lalujan, Virginia; Phangnesia, Calvin (APIC, 2024)
Just-In-Time production system in the form of kanban has been implemented in many production processes in order to optimize the production output. Internet of Things (IoT) has been integrated into production system in digitalizing production processes as well as obtaining and gathering real-time information in the factory floor through sensors, actuators, and network. In this study, an application of IoT into kanban and production system was proposed. The proposed electronic kanban system composed of Radio Frequency Identification (RFID) cards and readers, QR code and reader, microcontrollers, digital displays, and server. In this system, the kanban card is replaced by an RFID card. All workstations in the production process are equipped by RFID readers, microcontrollers, and displays to show relevant instructions to the operator. The microcontrollers are connected to a server to send information of the RFID card scanned by them and the time when the card was scanned. The latter information is used for tracing each of the products produced in each of the workstations. The proposed electronic Kanban system was implemented to an assembling process consisting of 7 workstations. The system was able to replace the conventional kanban card with RFID and electronic displays and performing the unit tracing capability.